Penanggulangan Praktik Plagiarisme Dunia Pendidikan Pada Era Literasi Digital: Penanggulangan Praktik Plagiarisme Dunia Pendidikan Pada Era Literasi Digital - Padel agam (Institute of Information Technology and Social Science (IITSS), 2020)
Plagiarism among students is increasingly becoming a serious concern along with the current development of digital literacy with advances in information and communication technology. The rampant practice of plagiarism can harm not only individual students, but also damage the integrity of education as a whole, starting from the formation of students' character, habits and intelligence. This research aims to identify and implement effective plagiarism prevention strategies in the digital literacy era. The research method involves analysis of the latest literature consisting of a number of journals from previous researchers. Awareness of the consequences of plagiarism, implementation of academic honesty, curriculum design and use of plagiarism detection technology are included as part of the response approach. Efforts to create an educational climate that supports academic integrity, training in the correct use of information sources, and promotion of ethical writing practices are also the focus of research. It is hoped that the results of this research can provide practical guidance for educators and educational institutions to increase students' awareness of plagiarism, prevent plagiarism practices, and promote positive digital literacy.